Relation of psychological well-being with coping strategies and family satisfaction in university students during the pandemic - Marín Medina, Claudio Ernesto (2023)
The pandemic generated a series of social alterations that affected people’s mental health. Analyzing psychological well-being and its possible associated factors in an abnormal situation such as the one experienced is of great scientific interest. For this reason, this research seeks to analyze the relationship of psychological well-being with coping strategies and family satisfaction in university students. The research has a quantitative approach, with a correlational scope and a cross-sectional non-experimental design. The sample is 377 students from a Chilean university. The Ryff psychological well-being scale, the COPE-28 coping strategies inventory and the FACES IV family satisfaction scale were applied. The results show that, on average, psychological well-being is at a medium to high level. In addition, it is evident that there is a significant correlation of psychological well-being with most coping strategies and with family satisfaction.